Percutaneous epididymal sperm aspiration and short time insemination in the treatment of men with obstructive azoospermia - Jiang, Yan (Springer US, 2013)
OBJECTIVE: To study the efficacy of percutaneous epididymal sperm aspiration (PESA) in combination with short time insemination to treat infertile men with obstructive azoospermia (OA). DESIGN: Paired randomized controlled trial in which each couple’s cohort of oocytes was divided into two equal groups. SETTING: Center for reproductive care. PATIENTS: Twenty men with OA. INTERVENTIONS: Motile spermatozoa were collected using PESA. Half of the oocytes were used for intracytoplasmic sperm injection (ICSI). The rest were inseminated briefly with PESA sperm in vitro fertilization (IVF). After 4–5 h, the remaining cumulus cells were removed mechanically for second polar body observation to decide whether to apply “rescue” ICSI (RE-ICSI). MAIN OUTCOME MEASURES: Rates of oocyte maturation, fertilization, cleavage, and good quality embryos. Numbers of available embryos and good quality embryos were compared between PESA-IVF (using a short incubation protocol + rescue ICSI) group and PESA-ICSI group. RESULTS: In the short time insemination group, cumulus cells were dispersed by PESA spermatozoa. No second polar bodies were found, so RE-ICSI was done. PESA-IVF + RE-ICSI and PESA-ICSI outcomes were comparable in terms of fertilization rates, 2PN cleavage rate and good quality embryo rates with no statistically significant differences. CONCLUSIONS: PESA sperm without centrifugation could disperse the cumulus cells but were infertile and therefore could substitute for synthetic hyaluronidase. The outcomes of PESA-IVF with rescue ICSI were equivalent to PESA-ICSI. Using spermatozoa obtained by PESA and IVF before RE-ICIS is a viable treatment for men with OA.